Association of high organochlorine pesticide serum levels with oxidative stress in intestinal metaplasia and gastric cancer - Gholamreza Asadikaram; Mohammad Reza Ashrafi; Sodaif Darvish Moghaddam; Moslem Abolhassani; Fatemeh Bagheri (Heliyon)
It has been revealed that certain organochlorine pesticides may increase the risk of gastric cancer incidence among farm workers. This research aimed to assay levels of 7 different organochlorine pesticides in the serum of functional dyspepsia, intestinal metaplasia and gastric cancer patients, along with measuring oxidative stress parameters compared to the control group and their associations. The levels of organochlorine pesticides in the serum of gastric cancer (n = 34), intestinal metaplasia (n = 8), functional dyspepsia patients (n = 48) and control group (n = 46), were measured by gas chromatography equipment. Oxidative stress parameters and erythrocyte acetylcholine esterase activity were also measured in these individuals. The levels of some organochlorine pesticides in the serum of gastric cancer patients were significantly higher than those in the control group. Moreover, the profiles of organochlorine pesticide concentrations were different in gastric cancer, intestinal metaplasia and functional dyspepsia patients. Overall, oxidant parameters were significantly higher in gastric cancer and intestinal metaplasia patients than those in functional dyspepsia patients and the control group, except in the case of malondialdehyde. The antioxidant and acetylcholine esterase enzyme activities were significantly higher in the control group than in other groups. Our results showed that progression from functional dyspepsia towards intestinal metaplasia and gastric cancer was associated with elevations in organochlorine pesticide serum levels, which had an association with the induction of oxidative stress and the reduction of antioxidant and acetylcholine esterase enzyme activities.